Adherence and activation of human mesenchymal stromal cells on brushite coated porous titanium - Osama A. Hamed; Mohammad Ehtisham Khan; Anwar Ulla Khan; Gulam Rabbani; Mohammad S. Alomar; Abdullateef H. Bashiri; Waleed Zakri (Results in Engineering, 2023)
Tri-calcium-phosphate Ca3(PO4)2 is considered a promising material to improve implant and bone tissue linking. Titanium (Ti), a highly porous material, was coated with crystalline brushite using an electrochemical process so that it could be used as an implant material. The aim of this research is to get a faster ingrowth of bone-tissue inside the porous structure. The crystalline coating was characterized by the standard XRD and SEM techniques. Additionally, the phase evolution of Ca3(PO4)2-crystals with different kinds of sterilization techniques was observed. In-vitro tests on the biocompatibility of the coating were done with human mesenchymal stem cells (HMSCs). The HMSCs are the most promising cell type for regenerative medicine and tissue engineering owing to their ability to differentiate into several tissues, such as, bone, cartilage, tendon, and muscle. For the treatment of local bone defects expanded HMSCs could be loaded on Ca3(PO4)2 coated metallic matrices and delivered to the target site. A possible application is brushite-coated porous titanium as a carrier matrix. To determine whether cell functions of HMSCs are influenced by the brushite surface, HMSCs were cultured on brushite-coated and uncoated porous titanium specimens. The viability and proliferation of HMSCs were successfully analyzed. Additionally, the release of cytokines (IL-6, IL-8, IL-11) were quantified as a marker of cell activation. The viable cells could be detected on specimens after 48 h initial seeding. After 8 days cell number on both specimens increased, although the proliferation on brushite-coated titanium was decreased compared to the uncoated surfaces. The release of both, IL-8 and IL-11 increased significantly due to the cultivation of HMSCs on the coated specimens for 8 days.